2007
DOI: 10.1007/s00542-007-0394-1
|View full text |Cite
|
Sign up to set email alerts
|

Two photon absorption coefficients and processing parameters for photoresists

Abstract: The two photon absorption (TPA) process is currently used to write high resolution microstructures for a variety of applications. Key parameters required to predict the final structure formation for this process are experimentally determined and reported in this article for two commercially available resists, Ormocore and SU-8. The measured TPA coefficients measured at 800 nm for Ormocore and SU-8 are 27 ± 6 and 28 ± 6 cm TW -1 , respectively. For Ormocore and SU-8 the dose required to write 35 and 50 lm high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The desired 3D structure is fabricated via two-photon absorption and subsequent photopolymerization, followed by removal of the unreacted liquid resin by a solvent. In two-photon absorption (TPA), changes of the physical or chemical properties of the resin are quadratically dependent on the intensity of the laser beam, such that the rate at which two-photon dye molecules are excited decreases rapidly (as z −4 ) with the distance from the focus and the excitation is confined in a small volume around the focus (on the order of λ 3 , where λ is the wavelength of the incident beam). Therefore, two-photon lithography not only allows for fabrication of structures that are difficult to access by conventional single-photon processes but also offers greater spatial resolution than other 3D microfabrication techniques by far. , By taking advantage of such a quadratic dependence of TPA probability on the photon fluence density and radical scavenger from dissolved oxygen molecules near the focal volume, Kawata et al demonstrated a subdiffraction-limit spatial resolution of 120 nm using a Ti:sapphire laser (λ = 780 nm) .…”
Section: Chemistry For 3d Fabrication Of Photonic Structuresmentioning
confidence: 99%
“…The desired 3D structure is fabricated via two-photon absorption and subsequent photopolymerization, followed by removal of the unreacted liquid resin by a solvent. In two-photon absorption (TPA), changes of the physical or chemical properties of the resin are quadratically dependent on the intensity of the laser beam, such that the rate at which two-photon dye molecules are excited decreases rapidly (as z −4 ) with the distance from the focus and the excitation is confined in a small volume around the focus (on the order of λ 3 , where λ is the wavelength of the incident beam). Therefore, two-photon lithography not only allows for fabrication of structures that are difficult to access by conventional single-photon processes but also offers greater spatial resolution than other 3D microfabrication techniques by far. , By taking advantage of such a quadratic dependence of TPA probability on the photon fluence density and radical scavenger from dissolved oxygen molecules near the focal volume, Kawata et al demonstrated a subdiffraction-limit spatial resolution of 120 nm using a Ti:sapphire laser (λ = 780 nm) .…”
Section: Chemistry For 3d Fabrication Of Photonic Structuresmentioning
confidence: 99%
“…After the development process, as shown in Figure 4-1 (b), the exposed pattern of lines converts into polymerized parallel ribs and the spacing between two consecutive lines into the fluidic channels. Unlike any lithography technique, which is governed by single-photon absorption (SPA), femtosecond laser irradiation via TPA has threshold and nonlinear behavior, because the absorbed energy is proportional to the square of the intensity of light [59]. In addition, the photoinitiation threshold is precisely confined in TPA polymerization for SU-8 resist.…”
Section: Fabricating Fluidic Channels Between Two Adj Ecent Polymerised Ribsmentioning
confidence: 99%
“…The effective number of pulses, N eff is a convenient measure of the feed rate in order to compare the results to stationary process of polymerization by multiple pulses. N eff can be calculated from [59,62]:…”
Section: Figure 4-3: Threshold Fluence and Number Of Effective Pulse For A For Various Repetition Rates; Inset Figure Represents Average mentioning
confidence: 99%